Towards the Internet of Robotic Things: Analysis, Architecture, Components and Challenges - Afanasyev, Ilya; Mazzara, Manuel; Chakraborty, Subham; Zhuchkov, Nikita; Maksatbek, Aizhan; Yesildirek, Aydin; Kassab, Mohamad; Distefano, Salvatore (IEEE, 2019)
The Internet of Things (IoT) and Robotics cannot be considered two separate domains these days. The Internet of Robotics Things (IoRT) is a concept that has been recently introduced to describe the integration of robotics technologies in IoT scenarios. As a consequence, these two research fields have started interacting, and thus linking research communities. In this paper we intend to make further steps in converging the two communities and broaden the discussion on the development of this interdisciplinary field. The paper provides overview, analysis and challenges of possible solutions for the Internet of Robotic Things, discussing the issues of the IoRT architecture, and the integration of smart environments and robotic applications.
Keywords: Computer Science